Kajian Investigasi Potensi dan Eksplorasi Morfologi Gumuk di Kabupaten Jember Menggunakan Penginderaan Jauh: Indonesia - Irawan, Januar Fery; Haeruddin; Aminah, Siti; Aji DS, Fanteri; Ulum, Miftakhul (UII, 2024)
Hummock is a typical morphology that is not found anywhere except in the active mountains. This uniqueness is due to the isolated hill shape with plain morphology formed in the geological setting. The existence of Gumuks dissiminated in Jember has been mined, causing their numbers to decrease drastically. Hummock in Jember district has a unique hill-shaped landscape with a height of over 2 meters. Hummocks in Jember are arranged from Raung Mount to the southwest to Jember Regency. There are several types (three) types of dunes that differ from the type of rock contained, namely rock dunes, coral dunes and sand dunes. At this moment, the existence of Hummock has been partially used for building material needs. The problem faced now is that the potential for piles other than as a building material requirement has not yet been researched. Therefore, effective management is needed through the identification of potential dunes through green mining research so that environmental problems are minimized when dune exploration is carried out. The purpose of this study was to find a green mining-based dune exploration technology, so that the treatment of each dune can be carried out appropriately. The stages of the research were carried out by observing the images. After the observations are made, field data is needed to validate and verify the pattern of dune. The research used remote sensing with guided techniques based on data in the field and geological maps. Based on remote sensing results it was found that there were 4 Classes in Land Use Change after Mining Operation carried out by people around the mine site.